CMV-Responsive CD4 T Cells Have a Stable Cytotoxic Phenotype Over the First Year Post-Transplant in Patients Without Evidence of CMV Viremia - Higdon, Lauren E.; Ahmad, Ayah A.; Schaffert, Steven; Margulies, Kenneth B.; Maltzman, Jonathan S. (Frontiers in Immunology, 2022)
Cytomegalovirus (CMV) infection is a known cause of morbidity and mortality in solid organ transplant recipients. While primary infection is controlled by a healthy immune system, CMV is never eradicated due to viral latency and periodic reactivation. Transplantation and associated therapies hinder immune surveillance of CMV. CD4 T cells are an important part of control of CMV reactivation. We therefore investigated how CMV impacts differentiation, functionality, and expansion of protective CD4 T cells from recipients of heart or kidney transplant in the first year post-transplant without evidence of CMV viremia. We analyzed longitudinal peripheral blood samples by flow cytometry and targeted single cell RNA sequencing coupled to T cell receptor (TCR) sequencing. At the time of transplant, CD4 T cells from CMV seropositive transplant recipients had a higher degree of immune aging than the seronegative recipients. The phenotype of CD4 T cells was stable over time. CMV-responsive CD4 T cells in our transplant cohort included a large proportion with cytotoxic potential. We used sequence analysis of TCR to identify clonal expansion and found that clonally expanded CMV-responsive CD4 T cells were of a predominantly aged cytotoxic phenotype. Overall, our analyses suggest that the CD4 response to CMV is dominated by cytotoxicity and not impacted by transplantation in the first year. Our findings indicate that CMV-responsive CD4 T cells are homeostatically stable in the first year after transplantation and identify subpopulations relevant to study the role of this CD4 T cell population in post-transplant health.